The assistance of Pesanggem in the Prevention of Coffee Pests through Vegetable Pesticides Coffee from Amethyst Mountain (Brugmansia Suaveolens Bercht. & J. Presl) at Taman Kehati Sapen Nusantara Mount Arjuno Pasuruan: Pendampingan Pesanggem dalam Pencegahan Hama Kopi melalui Pestisida Nabati Kopi dari Kecubung Gunung (Brugmansia Suaveolens Bercht. & J. Presl) di Taman Kehati Sapen Nusantara Gunung Arjuno Pasuruan - Wibisono, Mulyono; Fafit Rahmat Aji; Amang Fathurrohman; Endik Deni Nugroho (Jurnal Soeropati, 2022)
Pesanggem Taman Kehati Sapen Nusantara (TKSN) is a farming community in the Sapen Forest Area of ​​Mount Arjuno, Pasuruan. Coffee agroforestry is the main commodity for forest farmers in the TKSN area. For pest prevention, they have been using chemical pesticides to prevent the Coffee Fruit Borer. Through the Community Based Research approach, the companion team together with the community have succeeded in innovating vegetable pesticides coffee by utilizing Brugmansia Suaveolens Bercht. & J. Presl and Swietenia macrophylla King. as the main ingredients that are easily found in Taman Kehati Sapen Nusantara into environmentally friendly coffee pesticide products.